The “Big Two” in Hiring Discrimination: Evidence From a Cross-National Field Experiment - Susanne Veit; Hannah Arnu; Valentina Di Stasio; Ruta Yemane; Marcel Coenders (Personality and Social Psychology Bulletin, 2022)
We tested whether signaling warmth and competence (“Big Two”) in job applications increases hiring chances. Drawing on a field experimental data from five European countries, we analyzed the responses of employers (N = 13,162) to applications from fictitious candidates of different origin: native candidates and candidates of European, Asian, or Middle-Eastern/African descent. We found that competence signals slightly increased invitation rates, while warmth signals had no effect. We also found ethnic discrimination, a female premium, and differences in callbacks depending on job characteristics. Importantly, however, providing stereotype signals did not reduce the level of ethnic discrimination or the female premium. Likewise, we found little evidence for interactions between stereotype signals and job demands. While speaking against the importance of “Big Two” signals in application documents, our results highlight the importance of group membership and hopefully stimulate further research on the role of in particular ethnic stereotypes for discrimination in hiring.
doi:10.25384/SAGE.14175550.v1
Keywords: 300; stereotypes; hiring discrimination; field experiment; ethnic minorities